Types and Functions of Illocutionary Acts Used by the Main Characters in Neil Gaiman’s Coraline: A Pragmatic Study - Ramadhani, Indah Suci; Matoyah, Sri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Pragmatics examines how meaning is conveyed through context and interaction, particularly through speech act theory. This study aims to identify and analyze the types and functions of illocutionary acts used by the main characters in Neil Gaiman’s novel Coraline. The research employed a qualitative descriptive method to provide a detailed explanation of how characters express intentions through their utterances. The data consisted of fifty selected utterances produced by Coraline, the Other Mother, Coraline’s parents, the Cat, and the ghost children. Data were collected using documentation and purposive sampling techniques, focusing on utterances that clearly contain illocutionary acts. The analysis was conducted based on Searle’s classification of illocutionary acts, which includes assertive, directive, commissive, expressive, and declarative acts. The findings reveal that assertive and directive acts dominate the dialogues in the novel. Assertive acts are used when characters state facts, describe situations, or express beliefs, while directive acts appear when characters give commands, requests, or advice to influence others’ behavior. Commissive acts occur in moments where characters show commitment, such as making promises or threats, and expressive acts are found in emotional interactions that convey feelings like fear, anger, disappointment, or gratitude. Declarative acts occur less frequently, but they still play significant roles, especially in building narrative conflict and creating turning points in the storyline. Overall, the use of illocutionary acts in Coraline highlights how context and character relationships shape meaning and support the development of the plot.